Investigando a relação entre autoconceito, autoeficácia e autoestima: construção de evidências a partir da escala de cognições acadêmicas autorreferentes - Bianca Cristine Gomide Costa (2014)
This dissertation consists of two studies that investigate the relationship between self-concept, self-esteem and self-efficacy. The first study proposes the development of a Self-referential Academic Cognitions Scale to investigate the structural validity of self-concept, self-esteem and self-efficacy. The scale was administered to 812 high school students, average age of 16.5 years (SD = 1.25), on with 378 (46.55%) were men and 434 (53.45%) women, from three state public schools and a private school in the city of Belo Horizonte, state of Minas Gerais, Brazil, as well as from a federal public school and a private school in the city of Viçosa, state of Minas Gerais, Brazil. 12 theoretical models on the relationship between the variables of the study were developed and tested. The technique of Structural Equation Modeling was applied, and the degree of fit of models was assessed by the Comparative Fit Index (CFI) e Root Mean Square Error Approximation (RMSEA) indices. Of the 12 models tested, two had adequate degree of fit to the data and were suggested as possible solutions to the issue. Due to the presence of two models, the need for further analysis to select the best model was pointed. In the second study, the two models from the previous study were analyzed for their dimensional invariance by of groups gender, school type and school year. Named Classical Hypothesis Model and Alternative Hypothesis Model they represent two alternatives regarding the solution of the relationship between the various self-referential cognitions. For the invariance analysis, the second study sample was derived from the previous study, the total sample was used, including cases with missing data. Thus the sample consisted of 837 high school students, average age of 16.53 years (SD = 1.24), with 388 (46.36%) men and 449 (53.64%) women. The two models tested presented problems in their invariance, but with evidence of best fit of the Alternative Hypothesis Model compared to the Classical Hypothesis Model